Pengaruh Minat dan Penggunaan Metode terhadap Hasil Belajar IPA Biologi Siswa Kelas VII SMP Negeri 2 Jayapura - Mikael Nesi; Maik Akobiarek (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2018)
This study aims to determine the effect of interest and learning methods of Word Square Student Worksheet (LKS) on the learning outcomes of Biology Science VII grade students of SMP Negeri 2 Jayapura. The study population was all grade VII students of SMP Negeri 2 Jayapura. The sample of this study were students of class VIIJ, VIIK, and VIIL which were divided into 4 classes. Data analysis used prerequisite tests with parametric analysis paths with normality testing, homogeneity testing, and interest questionnaire variable data. Whereas hypothesis testing uses two-way anava. The results showed (1) There is an influence of interest arising from within students on learning outcomes achieved in the learning process with the results of the calculation of the variable high interest on average 74.87 and the variable low interest on average 65.04. (2) There is an influence on the average learning outcomes of Biology Science in students taught using the Word Square Model Student Worksheet (LKS) than students taught using the lecture method to students who have high interest results Fcount = 2,967> Ftable = 2.46. (3) There is a difference in the average effect of learning outcomes in Biology Natural Sciences in students taught using the Word Square Model Student Worksheet (LKS) than students taught using the lecture method to students who have low interest results Fcount = 2.952> Ftable = 2.46. (4) There is a very significant influence between the learning method and the interest or the effect of the method on the learning outcomes of Natural Sciences in Biology depending on the students' interest. The result is Fcount = 3.776> Ftable = 2.46. Keywords: word square model, interests, learning outcomes